Electrothermal combined optimization on notch in air-cooled high-speed permanent-magnet generator - Zhang, Xiaochen; Li, Weili; Baoquan, Kou; Cao, Junci; Cao, Haichuan; Gerada, C.; Zhang, He (Institute of Electrical and Electronics Engineers, 2014)
A 30kVA, 96000rpm, air cooled high-speed permanent magnetic generator (HSPMG) is investigated in this paper. Considering effects on both the magnetic circuit and heat transfer paths comprehensively, the stator slot notch in this HSPMG is optimized. First, by using the time-stepping finite element method, the transient electromagnetic fields of HSPMG is numerically calculated, and the electromagnetic losses in different components are obtained. Then, after the determination of other mechanical losses in such a machine, a three-dimensional fluid-thermal coupling calculation model is established, and the working temperature distribution in the HSPMG is studied. Thus, the electromagnetic-fluid-thermal coupling analysis method on the HSPMG is proposed, by using which the influences of machine notch height on machine magnetic circuit and cooling air flowing path are investigated. Meanwhile, both the electromagnetic performance and the temperature distribution in HSPMG with different stator notch height are studied, and a series of analytical equations are deduced to describe the variations of machine performances with stator notch. By using the proposed unbalance relative weighting method, the notch height is optimized to enhance the performance of HSPMG. The obtained conclusions could provide reference for HSPMG electromagnetic calculation, cooling system design, and optimization design.